Violent Behavior and Social Network Antisocial and Prosocial Behaviors - Cheung, Chau Kiu Jacky (Crime & delinquency, 2024)
While the youth’s social network has affected violent behavior, the influences of different kinds of networks and their behaviors have been unclear. Accordingly, the antisocial and prosocial of the peer friend (less than 5 years older or younger) network, elder friend (aged > 40 years) network, and the linking or resourceful network are likely influential based on social learning, social bond, and social capital theories. For a contest of the network behaviors, this study surveyed 2,363 youths (aged 16–24 years) in the Chinese society of Hong Kong. Results reveal that the prosocial behavior of peer and elder networks significantly inversely predicted the youth’s violent behavior, whereas the antisocial behavior of the linking network was significantly positively predictive. These network effects were not significantly different between the migrant and native and between the younger (aged below 20 years) and older (aged 20+ years) youths. The results imply the value of preventing the youth’s violent behavior by raising the youth’s bonding with prosocial friends and preventing the youth’s antisocial linking network with the guidance of the theories.